Shape of Training Review: an impact assessment for UK gastroenterology trainees. Issue 4 (5th March 2019) - Clough, Jennifer; FitzPatrick, Michael; Harvey, Philip; Morris, Liam
Abstract : Background: Physician training in the UK is undergoing considerable change due to the implementation of recommendations made in the Shape of Training Review. In particular, higher specialty training (HST), including gastroenterology, will be shortened from 5 to 4 years. This will also incorporate general internal medicine (GIM) training. There is concern among gastroenterologists regarding how high-quality gastroenterology training will be delivered in 4 years. Methods: The 2018 British Society of Gastroenterology (BSG) trainees' survey results were used to examine the potential impact of a 4-year HST period on achieving key competencies in gastroenterology. Results: 291 (49.4%) gastroenterology trainees responded. Satisfaction with gastroenterology training was high (79.6% respondents), and self-reported confidence in hepatology training was also high (84% senior respondents). However, only half (51.1%) of the respondents achieved complete colonoscopy certification by their final year of training. Comparison with the 2014 BSG trainees' survey demonstrated that the number of endoscopy procedures achieved by trainees has reduced in sigmoidoscopy (p=0.006) and colonoscopy (p<0.001). The proportion of time spent in GIM training has increased since the last survey, with 81.8% of the respondents spending more than 25% of their time in GIM. GIM training was reported to be a key barrier to adequate gastroenterology and endoscopy training. Conclusion: These data indicate significant barriers to delivering gastroenterology and endoscopy training within the current 5-year programme. Novel strategies will be required to improve the rate of progression in endoscopy training, in particular if high-quality gastroenterology HST training is to be delivered in 4 years.